2019
DOI: 10.1002/aoc.4819
|View full text |Cite
|
Sign up to set email alerts
|

Tandem magnetization and post‐synthetic metal ion exchange of metal–organic framework: Synthesis, characterization and catalytic study

Abstract: For the first time, metal‐exchange in a magnetic metal–organic framework (MOF) via tandem magnetization and post‐synthetic modification has been developed. The new magnetic mixed‐metal metal–organic framework nanocomposite, CoFe2O4/[Cu0.63/Zn0.37‐TMU‐17‐NH2] (CoFe2O4/[Cu/Zn‐MOF]) has been synthesized by immersing the CoFe2O4/Zn‐TMU‐17‐NH2 (CoFe2O4/Zn‐MOF) as a template in DMF solution of Cu (II) salts. CoFe2O4/[Cu/Zn‐MOF] showed to be a highly reactive and easily recoverable magnetic catalyst for the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Conversely, it is an excellent way to add the MNPs which has been previously formed to the solution containing the inorganic metal ions and organic ligands of the desired MOFs. According to the structure of the MFCs, this idea can be divided into: embedding method, Layer‐by‐Layer (LbL) growth method and encapsulation method . Among them, the LbL method can obtain MFCs having a core–shell structure, and usually can control the size.…”
Section: Preparation Magnetic Framework Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it is an excellent way to add the MNPs which has been previously formed to the solution containing the inorganic metal ions and organic ligands of the desired MOFs. According to the structure of the MFCs, this idea can be divided into: embedding method, Layer‐by‐Layer (LbL) growth method and encapsulation method . Among them, the LbL method can obtain MFCs having a core–shell structure, and usually can control the size.…”
Section: Preparation Magnetic Framework Compositesmentioning
confidence: 99%
“…The resulting framework composites had approximately 2.5 wt % of nanofiber for a 100 % yield reaction. Also CoFe 2 O 4 , Nobakht et al . first tandem the magnetization and post‐synthetic modification to prepare mixed‐metal MFCs‐CoFe 2 O 4 /[Cu/Zn‐MOF].…”
Section: Preparation Magnetic Framework Compositesmentioning
confidence: 99%
“…Theactivity of the homometallic and the Cu-Zn MM-MOFs was tested in the synthesis of tetrazole derivative from benzaldehyde,h ydroxylamine and sodium azide. [110] The catalytic data indicated that Another possible advantage of MM-MOFs in catalysis is the development of stable materials due to the presence of one metal, while the role of the second is to act as catalytic center. One example of this case is the use of MIL-101(Cr,Fe) as solid Lewis acid.…”
Section: Kurzaufsätzementioning
confidence: 99%
“…[30][31][32][33] As BMOFs have catalytic centers and can be easily recycled and reused several times, they have been interestingly applied in catalytic processes. [34][35][36][37][38][39] The catalytic effects of many BMOFs have been previously reported in different fields, including multicomponent reactions, [39] photocatalytic performance, [40] coupling, [41,42] and oxidative degradation reactions. [43] In addition, the synthesis of 2,4-disubstituted quinoline, [44] cyclohexenones, [45] functionalized dihydro-2-oxopyrroles, [46] and Suzukie Miyaura cross-coupling [47] has been made possible by BMOFs.…”
Section: Introductionmentioning
confidence: 99%